As figurações da morte e da memória na poética de Manoel de Barros - Martins, Waleska Rodrigues de Matos Oliveira [UNESP] (2015)
In describing the figurations involving the Death and Memory in Manoel de Barros' poetic work, the intention is establish the link between the perspective of transmutation and presentification. The main chiasmus of human existence is about life vs. death, always proves beneficial to the first. Naturally, the death is constituent perspective of humans. All societies face the death in different ways. However, the relationship between the death and human being can be expressed as fear or tranquility. Either as a rite of passage, or as an organic decomposition, the theme of death always involves a relationship between mankind and its paradigms, at any time. Such as complex as death, the Memory activates reminiscences, makes a person experiences old feelings again, retakes and makes present sensations. In a dialogue with the imagination of poets and writers, the Memory confirms facts, however without becoming a reality. Death and Memory put the Life in a singular movement. The poetic work of Manoel de Barros has like main themes the useless things, persons in connection with nature, childhood, his origin, men outside of capitalism, crazy and helpless people. But, other perspective dares to show in Manoel de Barros's poetry: the Death. The poet makes his discursive schemes about Death and Memory in a circular pattern. So, this thesis aims to understand the idea of Death and its figurations in Manoel de Barros' work, confronting with the perspective of Memory as Life presentification. Among the literary productions by said poet, the following works are selected for analysis: Poesias (1956), Menino do Mato (2010) and Escritos em verbal de ave (2011). The research methodology took into account procedures such as bibliographical and document survey on the life and works of Manoel de Barros. In addition, a search semantic provided the analysis approach. Subsequently, a media research about Manoel de Barros' interviews has been held. In the...